Pemberdayaan Masyarakat Tentang Ems (Emergency Medical Sistem) Sederhana Melalui Detections Pra-Hospital Stroke - Hasmita Hasmita; Mike Asmaria; Hilma Yessi; Trisna Kumala Sar; Prima Yoselina; Kheniva Diah Anggita; usrito Zalins Adecory (Jurnal Medika: Medika, 2026)
Stroke is a leading cause of death and disability that requires rapid treatment from the pre-hospital phase, but the community in Nagari Malai III Koto still has minimal knowledge regarding early detection and initial treatment of stroke. This community service program aims to improve the community's ability in pre-hospital management of stroke patients through simple EMS. Methods include assessment, participant identification, health education on early stroke detection using the FAST method, and an introduction to EMS with the Detection component. Participants were 19 elderly people at high risk of stroke and 17 family members. Evaluation results showed a significant increase: stroke knowledge from 35% to 90%, FAST simulation from 30% to 88%, family role from 40% to 92%, and understanding of the EMS process from 25% to 85%. The conclusion of this program is that community-based health education is effective in increasing community preparedness in pre-hospital stroke management, and is expected to be able to implement an emergency stroke referral system.